The relationship between extended foster care and college outcomes for foster care alumni. Issue 2 (14th March 2020) - Okpych, Nathanael J.; Courtney, Mark E.
ABSTRACT: The federal Fostering Connections law gives states the option to increase the foster care age limit from age 18 up to age 21. This law could potentially improve postsecondary education outcomes for youth in foster care. We analyze data collected from a longitudinal study of foster youth in three Midwestern states (n = 732). Linear probability models and instrumental variable models estimated the impact of years in care past age 18 on three outcomes: enrollment by age 21, persistence by age 21, and degree completion by age 29/30. Results indicated that each year in care past age 18 is expected to increase enrollment by about 9 to 11 percentage points. Significant associations were not found for persistence or degree completion.